Lingkungan Keluarga, Lingkungan Sosial dan Pergaulan Teman Sebaya terhadap Hasil Belajar - Trianah; Pieter Sahertian (Jurnal Penelitian dan Pendidikan IPS, 2020)
Abstract Learning outcomes are changes in behavior obtained by students after experiencing learning activities. Learning outcomes include three domains, namely cognitive, affective and psychomotor. High and low learning outcomes achieved by students are influenced by factors of the family environment, social environment, and the association of students with peers. This study aims to analyze the influence partially (individually) or simultaneously (together) between the family environment, social environment and peer relationships simultaneously on learning outcomes. The method used is quantitative with explanatory research types and research samples of 69 students or 31% of the population taken using proportional random sampling techniques. The results showed that the family environment Social environment and peer relationships affect learning outcomes